2002
DOI: 10.1523/jneurosci.22-16-07218.2002
|View full text |Cite
|
Sign up to set email alerts
|

Compromised Hemodynamic Response in Amyloid Precursor Protein Transgenic Mice

Abstract: APP23 transgenic mice overexpressing amyloid precursor protein (APP751) reproduce neuropathological changes associated with Alzheimer's disease such as high levels of amyloid plaques, cerebral amyloid angiopathy, and associated vascular pathologies. Functional magnetic resonance imaging (fMRI) was applied to characterize brain functionality in these mice through global pharmacological stimulation. The cerebral hemodynamic response to infusion of the GABA(A) antagonist bicuculline was significantly reduced in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
77
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 38 publications
3
77
0
Order By: Relevance
“…Reduced blood flow has been reported as one of the most consistent physiological deficits in AD (9, 10); however, it remains unclear whether the reduced cerebral blood flow is a response to neuronal damage or a factor initiating the characteristic neuropathology. In vivo studies showed the effect of A␤ on cerebral blood flow and vessel architecture in a mouse model for AD (11,12). In other models, cerebrovascular regulatory mechanisms, such as endothelium-dependent relaxation and cerebrovascular autoregulation, were altered before amyloid deposition (13-16).…”
mentioning
confidence: 99%
“…Reduced blood flow has been reported as one of the most consistent physiological deficits in AD (9, 10); however, it remains unclear whether the reduced cerebral blood flow is a response to neuronal damage or a factor initiating the characteristic neuropathology. In vivo studies showed the effect of A␤ on cerebral blood flow and vessel architecture in a mouse model for AD (11,12). In other models, cerebrovascular regulatory mechanisms, such as endothelium-dependent relaxation and cerebrovascular autoregulation, were altered before amyloid deposition (13-16).…”
mentioning
confidence: 99%
“…Ischemia commonly results in secondary injury, and can have significant acute effects in stroke (2,3) and traumatic brain injury (TBI) (4,5). Chronic effects of ischemia can also be observed in Alzheimer's disease (6,7). Similarly, hemorrhage (8) and brain tumors (9) can alter CBF, leading to deleterious neurological effects.…”
mentioning
confidence: 99%
“…As described above, Mueggler and co-workers (38,37) have reported reduced CBV response to pharmacological stimulation with bicuculline in aged APP23 mice, a model for human Alzheimer's disease. In an interesting approach, Small et al (141) analyzed contrast differences on T 2 Ã -weighted images, which vary with resting oxygen concentrations.…”
Section: Cognitive Studies With Fmri In Small Animalsmentioning
confidence: 80%
“…In the past, this was achieved with invasive blood sampling for repetitive blood gas analysis throughout the fMRI experiment. The drawbacks of limited blood sample availability and blindness to pCO 2 fluctuations between sampling periods have now been eliminated by using the continuous and non-invasive recording of transcutaneous pCO 2 (23,30,37,38) or end-tidal pCO 2 values with MRI-compatible capnometry in intubated animals (39)(40)(41) or simply with an inhalation mask (42) for which linear correlations with arterial pCO 2 have been established (43).…”
Section: Physiological Monitoringmentioning
confidence: 99%
See 1 more Smart Citation